Wacana Korupsi vs. Retorika Pajak: Etnografi Komunikasi Petugas PBB-P2 di Ruang Publik Desa - Muslim; Redi Panuju; Didik Sugeng W (Program Studi Ilmu Komunikasi, 2026)
This research is motivated by low PBB-P2 compliance in Tempuran Village, Pasrepan, caused by a public trust crisis. The study aims to analyze the clash between corruption discourse and tax rhetoric in village public spaces using Dell Hymes' SPEAKING model. Employing a qualitative ethnographic method, data were collected through observation and interviews at the village hall, residential porches, coffee shops, and social media. Findings reveal sharp fragmentation of meaning; formal spaces produce only pseudo-compliance, while informal spaces serve as hubs for symbolic resistance where corruption issues are used as a moral shield to delay taxes. In conclusion, corruption discourse acts as a communication noise distorting government development messages. It is recommended that the village government transform its communication strategy into a more persuasive and transparent approach within informal spaces to restore institutional credibility and voluntary compliance.